The spice lover's guide to herbs & spices : a comprehensive and opinionated guide to more than 200 herbs, spices and spice blends - Hill, Tony (New Jersey : Wiley, 2004)
A guide to herbs and spices. It profiles more than 125 herbs and spices, ranging from the familiar to the exotic. It gives practical information and advice, including how best to use nine popular chiles, what distinguishes true cinnamon from cassia cinnamon, and why it makes a difference where your bay leaf comes from.
SECTION ONE: PURE SPICES. 1. Ajwain. 2. Allspice. 3. Angelica. 4. Anise, Brown. 5. Anise, Black. 6. Anise-Hyssop. 7. Annatto. 8. Arrowroot. 9. Asafetida. 10. Avocado Leaf. 11. Barberry. 12. Basil. 13. Bay Leaf, Turkish. 14. Bay Leaf, Californian. 15. Bay Leaf, Indian. 16. Bay Leaf, Indonesian. 17. Black Lemon. 18. Black Salt. 19.Boldo Leaf. 20. Borage. 21. Bread Clover. 22. Bush Tomato. 23. Candle Nut. 24. Caraway. 25. Cardamom, Green & White. 26. Cardamom, Thai. 27. Cardamom, Black. 28. Catnip. 29. Celery. 30. Chervil. 31. Chicory. 32. Chiles. 33. Chives. 34. Cicely. 35. Cinnnamon, True Cinnamon. 36. Cinnnamon, Indonesian Cassia-Cinnamon. 37. Cinnnamon, Chinese Cassia-Cinnamon. 38. Cinnamon, White Cinnamon. 39. Cilantro. 40. Cloves. 41. Coriander, European. 42. Coriander, Indian. 43. Cream of Tarter. 44. Cubeb. 45. Culantro. 46. Cumin, Brown. 47. Cumin, Black. 48. Curry Leaf. 49. Dill. 50. Epazote. 51. Fenugreek. 52. Fennel. 53. Fingerroot. 54. Galangal, Greater. 55. Galangle, Lesser. 56. Gale. 57. Garlic. 58. Ginger. 59. Golpar. 60. Grains of Paradise. 61. Horseradish. 62. Hyssop. 63. Juniper. 64. Kaffir Lime. 65. Kencur. 66. Kokum. 67. Lavender. 68. Lemon Grass. 69. Lemon Myrtle. 70. Lemon Verbena. 71. Licorice. 72. Mace. 73. Mahleb. 74. Mango Powder. 75. Marjoram. 76. Mints. 77. Mitsuba. 78. Mountain Pepper. 79. Mugwort. 80. Mustard Seeds, Yellow, Brown, & Black. 81. Nigella. 82. Nutmeg. 83. Oregano, Mediterranean. 84. Oregano, Mexican. 85. Paprika. 86. Parsley. 87. Peppercorn, Black, Green, White,m & 'True" Red. 88. Peppercorn, Long. 89. Peppercorn, Negro. 90. Pepperleaf. 91. Pink Pepper Berries. 92. Pomegranate Seed. 93. Poppy. 94. Rose Petals. 95. Rosemary. 96. Saffron. 97. Safflower. 98. Sage. 99. Sassafras. 100. Savory, Summer & Winter. 101. Screwpine. 102. Sea Salts. 103. Sesame Seed. 104. Seaweed. 105. Shiso. 106. Sichuan Pepper. 107. Star Anise. 108. Sumac. 109. sweet Flag. 110. Sylphium. 111. Tarragon. 112. Tamarind. 113. Thyme. 114. Turmeric. 115. Vanilla Bean. 116. Vietnamese Coriander. 117. Wattle Seed. 118. Wasabi. 119. Zedoary. SECTION TWO: BLENDED SPICES. 1. Americas Blends. 2. Mexican Blends. 3. Central and South American Blends. 4. Caribbean Blends. 5. Northern European Blends. 6. Central European Blends. 7. Medieval Blends. 8. French Blends. 9. Mediterranean Blends. 10. Russian Blends. 11. Middle Eastern Blends. 12. Indian Subcontinent Blends. 13. African Blends. 14. Asian Peninsula Blends. 15. Chinese Blends. 16. Pacific Island Blends. 17. Japanese Blends.
Includes bibliographical references and index.
Keywords: COOKERY (HERBS)